Rare manifestation of a common infection: Immune thrombocytopenic purpura due to hepatitis-A - Dr. Jyothirmai Cheerla; Dr. Vinay Kumar Lakkoju; Dr. Lakshmi Sravanthi N.; Dr. Vijayalakshmi Bhimireddy (Pediatric Review: International Journal of Pediatric Research, 2019)
Hepatitis A virus (HAV) is a benign self-limiting gastro intestinal infection of the children belonging to developing countries. Haematological complications like immune thrombocytopenic purpura (ITP) is rarely reported as a manifestation of acute hepatis A infection. We report a 6 year old female child with bleeding manifestations diagnosed to have ITP associated with acute hepatitis A infection.